Histones deacetylases in the epidermis: structure, functions and therapeutic implications - Nguyen Van, Chloé; Lamartine, Jérôme (Frontiers in Epigenetics and Epigenomics, 2025)
Histone deacetylases (HDACs) are key epigenetic regulators that catalyze the removal of acetyl groups from histones and non-histone proteins, thereby modulating chromatin accessibility and gene expression. The HDAC family is composed of 11 HDACs and seven sirtuins that are all located within the epidermis. These enzymes are involved in essential cellular processes such as proliferation, differentiation, the regulation of immune function and wound healing, thus playing a central role in maintaining tissue homeostasis. This review aims to explore the mechanistic contributions of HDACs to epidermis physiology and investigate their involvement in the development of diseases such as psoriasis, atopic dermatitis and cancers. It also highlights the therapeutic potential of HDAC inhibitors, which are already used in oncology but whose application in dermatology is still emerging.